Molecular evolution and structural analysis of Caprine CD14 deduced from cDNA clones - PAL, ARUNA; CHATTERJEE, P N; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2013)
The study was conducted to characterize CD14 gene of goat (Capra hircus), an important molecule for innate immunity that can act against a wide range of pathogens. Cloning and sequence analysis of CD14 cDNA revealed 1, 119 nucleotide long open reading frame encoding 373 amino acids protein and 20 amino acids signal peptide. Caprine CD14 peptide (gene bank protein ID: ABE 68725.1) exhibited a high percentage of peptide identity (54.2–87.2%) with the corresponding mammalian homologs. In caprine CD14 68 distinguished nucleotide changes were identified and the site for mutational hot-spot was detected in caprine CD14 gene. Non-synonymous substitutions exceeding synonymous substitutions indicated the evolution of this protein through positive selection among domestic animals. Predicted protein structures obtained from deduced amino acid sequence indicated caprine CD14 molecule to be a receptor with horse shoe-shaped structure when exists as dimer and many grooves responsible for ligand binding.These studies revealed CD14 molecule of goat as a receptor with amino terminal pocket as the site for LPS binding. The sites for LPS binding, LPS signalling, leucine-rich repeats, putative N-linked glycosylation, O-linked glycosylation, glycosyl phosphatidyl inositol anchor, disulphide bridges, alpha helix, beta strand, leucine rich nuclear export signal, leucine zipper and domain linker were predicted. Most of leucine and cysteine residues remain conserved across the species.